MENINGKATKAN HASIL BELAJAR LARI CEPAT MENGGUNAKAN PERMAINAN KEJAR MENGEJAR PADA SISWA KELAS V SD (Department of Physical Education, Sport, Health and Recreation, 2015)
The purpose of this study to determine whether the use of learning sprinting chase chase game can improve student learning outcomes Class V SDN 01 Gandarum District of Pekalongan Kajen Year 2014 issues which are the subject of research as follows. This research is PTK using practice tests. Subjects were fifth grade students of SDN 01 Gandarum totaling 26 students, consisting of 17 boys and 9 girls. Instruments used observation and observation tests. The data analysis technique used in this study is to compare the data with the initial condition. The results of this study concluded that the learning using the game chase chase, can improve learning outcomes sprint. From the analysis of the first cycle is known percentage of 57.69% mastery learning student number 15, have increased in the second cycle of 100%, the number of completeness of 26 students. Advice given to teachers in the learning that is supposed to run faster using chase chase game because it can improve student learning outcomes. In addition, teachers also need to be more creative and innovative in the learning process).